2018
DOI: 10.3329/ajmbr.v4i1.36823
|View full text |Cite
|
Sign up to set email alerts
|

Productive and reproductive performances of Sheep at field level of Rajshahi and Mymensingh District of Bangladesh

Abstract: This study was undertaken to assess the reproductive performances of sheep at field level of Rajshahi and Mymensingh district of Bangladesh during January to December, 2016. A total of 52 farms (26 each in Rajshahi and Mymensingh) were selected for determining the reproductive parameters of ewes. Ewe lambs in Mymensingh reached puberty at significantly (P<0.03) younger age (186.9±18.4 days) than in Rajshihi (199.9±24.9 days). The average age at first pregnancy was 201.4±20.0 days in two regions. Similarly, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
(13 reference statements)
1
5
1
Order By: Relevance
“…The highest value was 7.99±0.01 month and the lowest was 6.06±0.01 month in Gobindogonj and Mohadevpur Upazila respectively. A similar result was found that the age at puberty or first heat varied from 5-10 months [7]. The age at 1 st lambing was found 12.65±0.03 months irrespective of areas and the highest value was 13.91±0.02 months found in Gobindogonj Upazila.…”
Section: Reproductive Performance Of Native Sheepsupporting
confidence: 80%
See 4 more Smart Citations
“…The highest value was 7.99±0.01 month and the lowest was 6.06±0.01 month in Gobindogonj and Mohadevpur Upazila respectively. A similar result was found that the age at puberty or first heat varied from 5-10 months [7]. The age at 1 st lambing was found 12.65±0.03 months irrespective of areas and the highest value was 13.91±0.02 months found in Gobindogonj Upazila.…”
Section: Reproductive Performance Of Native Sheepsupporting
confidence: 80%
“…The age at puberty was estimated as the age of the first estrus of the ewe. The sing is wagging tail, swelling, and mucus discharge from the vulva, jumping tendency to others, rubbing their body with the rams and remain closer to the rams [7].…”
Section: Age At 1 St Heat or Pubertymentioning
confidence: 99%
See 3 more Smart Citations